Anatomical peculiarities of the Giant Pterosaur Thanatosdrakon Amaru (Azhdarchidae, Pterodactyloidea) from upper cretaceous deposits of Mendoza, Argentina - Ortiz David, Leonardo Daniel (2022)
The largest South American pterosaur, Thanatosdrakon amaru, represents an excellent case study to analyze theimportance of expanding phylogenetic matrices withappendicular characters. Several phylogenetic results recoverThanatosdrakon deeply nested in the Azhdarchidae clade, as itpresents numerous characters in the humeri that are decisive inachieving these results. However, Thanatosdrakon presentsunique characters that evidence a greater diversity in theclassic morphologies described for azhdarchids. The preservedaxial sequence shows a remarkable development of neuralarches and very reduced vertebral centers. This structure ismaintained from the posterior cervical vertebra to thedorsosacral vertebrae. The proximal syncarpal has amorphology similar to those described for azhdarchids,however, it presents a developed posterodistal process.Finally, the characteristics of the wing phalanges are singular,lacking the ventral ridge observed in many azhdarchids.Preliminary histological analyses indicate that the smallestspecimen (UNCUYO-LD 307) is a juvenile-subadult, andthese characteristics could be due, in part, to the ontogeneticstage of the specimen. In azhdarchids, the characters related tothe skull and middle cervical vertebrae are crucial forphylogenetic resolutions. Taxa lacking these structures areshown to be unstable in topologies. Detailed characterizationson other elements, such as the humerus, have partly solvedthese problems. However, there is a need to expand thenumber of characters in appendicular elements that wouldallow improved resolutions in less inclusive clades.